Can physical education be used as an antidote to the negative effects of remote learning? - Umiastowska, Danuta (Contemporary problems of physical and health culture, 2022)
The situation of school, universities, parents, children and ourselves provokes us to consider the answer to the question: ‘What next?’. The organization of the life of learners and educators, which forced both parties to spend a long time in front of computer monitors, resulted in a significant reduction in the time devoted to physical activity. The closure of many institutions and restriction of access to sports and recreational infrastructure triggered creative mechanisms among many physical education teachers. In many cases, the parents’ view of the work of the school and teachers has changed. The presented work is a study devoted to the researcher’s reflections on the consequences of epidemiological limitations in our society.